185 Safety of Venous Thromboembolism Chemoprophylaxis Following Traumatic Intracranial Hemorrhage. (1st April 2022) - Boulter, Jason H.; Szuflita, Nicholas S.; Porambo, Michael; Dewar, Callum D.; Woodle, Samuel; Scanlon, Michaela; Shields, Margaret; Meister, Melissa; Brennan, Alexandra; Bailey, Zachary; Scultetus, Anke; Shear, Deborah; et al.
Abstract : INTRODUCTION: Post-traumatic brain injury (TBI) venous thromboembolic (VTE) disease represents a serious complication which occurs not infrequently given the hypercoagulable state of trauma. Unfortunately, VTE chemoprophylaxis has historically been limited by concerns for intracranial hemorrhagic expansion. METHODS: The Joint Trauma System was queried for United States service members with blast or penetrating TBIs. Data regarding demographics, injury characteristics, and VTE chemoprophylaxis administration were collected and the imaging database was searched for pre- and post-chemoprophylaxis head CTs. All identified hemorrhages were volumetrically analyzed and pre- and post-chemoprophylactic hemorrhage volumes were compared. RESULTS: 383 patients were identified from the Joint Trauma System. Of those, 136 patients were found to have 393 hemorrhages with a majority being intraparenchymal (55.0%). The mean hemorrhage volume was 3.2cc (SD = 8.1cc) with a mean time from injury to first chemoprophylaxis dose of 71.5 hours (SD = 36.2 hours). There was a significant reduction in volume between the pre- and post-chemoprophylaxis head CTs (3.2cc [SD = 8.1cc] vs 3.0cc [SD = 7.8cc], p = 0.024). When analyzed by time from injury to chemoprophylaxis, there was no difference for patients who received prophylaxis within 48 hours of injury (N = 95, pre: 2.2cc [SD = 4.2cc], post: 2.2cc [SD = 4.9cc], p = 0.964) or within 24 hours of injury (N = 27, pre: 1.8cc [SD = 3.9cc], post: 1.4cc [SD = 2.4cc], p = 0.304). Similarly, when patients were stratified by type of injury, there was no significant difference in hemorrhage volume after chemoprophylaxis administration in patients with closed (N = 137, pre: 1.8cc [SD = 4.2cc], post: 1.5cc [SD = 3.2cc], p = 0.180) or penetrating injuries (N = 233, pre: 4.1cc [SD = 9.5cc], post: 3.8cc [SD = 9.4cc], p = 0.068). Finally, an analysis of larger injuries (defined as hemorrhages greater than 5cc) demonstrated a significant reduction in hemorrhage volume following chemoprophylaxis administration (N = 64, pre: 14.8cc [SD = 14.4cc], post: 12.9cc [SD = 14.9cc], p = 0.003). CONCLUSION: These data suggest that administration of chemoprophylaxis within as little as 24 hours from hemorrhagic TBI does not result in hemorrhage expansion in closed or penetrating injuries irrespective of the volume of damaged tissue.